2021
DOI: 10.3390/futuretransp1030038
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Delivery Pattern through Floating Car Data: Empirical Evidence

Abstract: This paper investigates the opportunities offered by floating car data (FCD) to infer delivering activities. A discrete trip-chain order model (within the random utility theory) for light goods vehicles (laden weight less than 3.5 tons) is hence proposed, which characterizes delivery tours in terms of the number of stops/deliveries performed. Thus, the main goal of the study is to calibrate a discrete choice model to estimate the number of stops/deliveries per tour by using FCD, which can be incorporated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This phenomenon is the cause of the current explosion in urban freight publishing, both for shopping (e.g., [15,16]) and for delivery travels (e.g., [17,18]). Among these, there are studies focused on emerging technologies [19,20] or on the use of ecofriendly vehicles [21][22][23]. Studies that concentrate on service traffic, however, are less common, and can rely on trip generation [24], trip attraction [25], and parking [26].…”
Section: The Service Tripsmentioning
confidence: 99%
“…This phenomenon is the cause of the current explosion in urban freight publishing, both for shopping (e.g., [15,16]) and for delivery travels (e.g., [17,18]). Among these, there are studies focused on emerging technologies [19,20] or on the use of ecofriendly vehicles [21][22][23]. Studies that concentrate on service traffic, however, are less common, and can rely on trip generation [24], trip attraction [25], and parking [26].…”
Section: The Service Tripsmentioning
confidence: 99%
“…Precise data of the movements of freight vehicles and goods using new technologies (e.g., vehicles sensors) can be collected in a very large amount. For example, GPS (global position systems) historical data can be saved creating a very large data set, tendentially big (Antoniou et al, 2018;Comi and Polimeni, 2021;Nigro et al, 2022). Mehmood et al (2017) demonstrated how big data can be used to improve transport efficiency and lower externalities.…”
Section: Big Datamentioning
confidence: 99%
“…Therefore, the possibility given by the e-ICTs can move from fleet tracing (Comi and Polimeni, 2021), which allow companies to monitor and find out the gaps in statutory and regulatory requirements as well as to process real-time information on weather conditions, roadblocks, traffic congestion, or to plan a fuel-saving route. Therefore, ITSs, and more in general ICTs, include opportunity for each private (i.e., transport and logistics operators, retailers, and end consumers) or public actor (i.e., public administrations) to increase their own utility.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, authors describe a Dijkstra algorithm-based system to calculate the shortest route in a parking lot environment. And the paper in [33] investigates the opportunities offered by FCD to infer the number of delivering activities per tour with light good vehicles. The technology background adopts vehicle to everything (V2X) and driverless technologies.…”
Section: Literature Reviewmentioning
confidence: 99%